Effect of Acacia mearnsii Tannin Extract Supplementation on Reproductive Performance and Oxidative Status of South African Mutton Merino Rams - Osman Ahmed (MDPI AG, 2021)
We investigated the supplementation effects of Acacia mearnsii tannin extract (TE) and encapsulated tannin extract (ETE) on reproductive performance and oxidative status of South African Mutton Merino rams. We also observed the season effect on the testicular measurements. Thirty rams were divided into five groups: 0.0 g TE (control), 1.5 g TE, 3 g TE, 1.5 g ETE, and 3 g ETE supplemented daily for 16 weeks transiting from autumn to winter. Bodyweight and testicular measurements were recorded biweekly. Semen and blood samples were collected weekly during the last five weeks of supplementation. Results showed that the increase in the ETE from 1.5 to 3 g increased the testicular length and sperm concentration, as well as decreased the percentages of low and non-progressive spermatozoa (<semantics>p<0.05</semantics>). Simultaneously, the increase in the TE from 1.5 to 3 g decreased semen volume and elevated the percentage of abnormal sperm (<semantics>p<0.05</semantics>). The results suggest that the encapsulation of TE affords the maximum benefit of the TE on the sperm quality. Treatments did not affect the hormonal and oxidative status. Testicular measurements were significantly higher in autumn compared to winter. The plasma level of cortisol significantly correlates negatively with sperm motility, viability, and acrosome integrity.